Beneficial Alteration in Growth Performance, Immune Status, and Intestinal Microbiota by Supplementation of Activated Charcoal-Herb Extractum Complex in Broilers - Wang, Lixue; Zhang, Ying; Guo, Xiangyue; Gong, Limin; Dong, Bing (Frontiers in Microbiology, 2022)
The aim of this study was to examine the effects of activated charcoal-herb extractum complex (CHC) on broilers growth performance, inflammatory status, microbiota, and their relationships. A total of 864 one-day-old Arbor Acres male broilers (41.83  0.64 g) were distributed to eight dietary treatments with six replicates (18 birds per replicate), which were a corn-soybean meal based diet (NCON); basal diets supplemented with 250, 500, 750 or 1000 mg/kg CHC, and three positive controls; basal diets supplemented with 200 mg/kg antibacterial peptide (AMP), 200 mg/kg calsporin (Probio) or 500 mg/kg montmorillonite (MMT). The study period was 42 d including the starter (d 0-21) and grower (d 22-42) phases. Compared with the NCON group, CHC supplementation (optimal dose of 500 mg/kg) increased (P < 0.05) growth performance and tended to increase feed conversion rate in broilers. CHC (optimal dose of 500 mg/kg) decreased level of the interleukin-1β (IL-1β) and interferon-γ (IFN-γ) in serum, and improved the levels of immunoglobulins A (IgA) and immunoglobulins A (IgM) in serum, and secretory immunoglobulin A (SIgA) in the mucosa of duodenum and jejunum (P < 0.05). In the ileum, CHC supplementation decreased community abundance represented by lower Sobs, Chao 1, Ace, and Shannon compared with NCON (P < 0.05). At phylum level, CHC supplementation increased the abundance of Firmicutes, while decreased the abundance of Bacteroidetes in ileum and cecum (P < 0.05). At genus level, compared with NCON group, CHC markedly reduced (P < 0.05) the abundances of pathogenic bacteria Alistipes in ileum, which were negatively associated to the levels of SIgA and IL-1β in ileum mucosa. In conclusion, CHC had beneficial effects on the growth performance, immune status, and intestinal microbiota composition. CHC had dual functions of absorption like clays and antibacteria like antibacterial peptides.